Isolation and characterization of Plant Growth Promoting Bacteria (PGPB) at UiTM Kuala Pilah Forest Reserved / Normazni Abdul Wahab - Abdul Wahab, Normazni (2017)
The study was conducted at UiTM Kuala Pilah Forest Reserved at Negeri Sembilan, Malaysia. This study was started from September 2016 until December 2016. The objective for this study is to isolate and characterized plant growth promoting bacteria (PGPB) from root at UiTM Kuala Pilah reserved forest. The roots sample was taken and later being undergo serial dilution and plated on Nutrient Agar. The colonies with different morphology was proceed with gram staining, motility, hydrogen cyanide (HCN) production, ammonia production, catalase test, and salt tolerance test. 6 isolates was obtained from this experiment and most of them possessed more than one PGPB characteristics for each isolated. The potential PGPB was A1. Thus, UiTM Kuala Pilah forest reserved have potential PGPB.